A Solution for Implementing Partnership Contracts on the Blockchain Platform Using the Decentralized Finance (DeFi) and the IDO Method - Mohammad Yaghoubi; Vahid Seyfi (تحقیقات مالی اسلامی (پیوسته))
Examining the challenges of usury-free banking is one of the most important issues that the country is facing. One of the main challenges of the country's banking system is the implementation of partnership contracts. Due to the conflict between the characteristics of  partnership contracts and the nature of the bank, the correct implementation of these contracts in the banking system is difficult. Also, considering that the correct implementation of partnership contracts in the Islamic financial system can have many positive effects, there is a need to provide a suitable and alternative solution for their correct implementation. In this research, while stating the theoretical foundations and challenges of the banking system in the implementation of partnership contracts, we will present a suitable and alternative operating model on the blockchain platform using the Decentralized Finance (DeFi) and the Initial  Decentralized Exchange Offering (IDO) for the implementation of partnership contracts. . The proposed model is consistent with the most important features of partnership contracts, such as variable profit, participation , profit and loss sharing, and continuous monitoring of the good implementation of the project.